2010
DOI: 10.1111/j.1600-0706.2010.18320.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dispersal status on estimates of local population growth rates in a Temminck's stint Calidris temminckii population

Abstract: Due to different costs and benefits associated with dispersal and philopatry, life history traits of immigrants and philopatric individuals may differ. Despite of the apparent effects, dispersal status is only rarely considered in analyses of population dynamics. We analysed whether dispersal status explains variation in life history traits of an endangered Temminck's stint Calidris temminckii population breeding at the Baltic Sea. We also estimated the impact of immigration and dispersal status on the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
(100 reference statements)
0
21
1
Order By: Relevance
“…(2010) revealed that both natal and breeding dispersal seem to be rare at regional scale (5–50 km). Pakanen et al. (2010, 2011) also observed that individuals recruited to the population as immigrants were more likely to change breeding sites between seasons, especially if they had experienced poor breeding success.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…(2010) revealed that both natal and breeding dispersal seem to be rare at regional scale (5–50 km). Pakanen et al. (2010, 2011) also observed that individuals recruited to the population as immigrants were more likely to change breeding sites between seasons, especially if they had experienced poor breeding success.…”
Section: Discussionmentioning
confidence: 97%
“…In this case, receiving only very few immigrants might cause inbreeding , although in the Bothnian Bay there is evidence that immigration, even if occurring at a low rate, has likely saved the population from extinction so far (Rönkä et al. , 2008; Pakanen et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations